1993
DOI: 10.1111/j.1460-2695.1993.tb00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Fracture Mechanics Test Method Egf P1–87d (Esis P1–90/Esis P1–92): Analysis of an Experimental Round Robin

Abstract: — The elastic—plastic fracture mechanics test method EGF P1–87 D: EGF Recommendations for Determining the Fracture Resistance of Ductile Materials has been validated by an extensive round robin, covering fracture tests and their evaluation as well as scanning electron fractography. The results confirmed the suitability of the procedure, but suggested some modifications. The resulting procedure ESIS P1–90 was then further modified and its actual designation is ESIS P1–92. The present report provides comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…6 steel of different thicknesses and pre-crack depths, against those measured by nine point method to show that nine point method gives a fairly good estimate of the average SZW measured over closer intervals. Schwalbe et al (1993) has similarly concluded on the basis of round 46 S. Bansal et al The variations of SZW, obtained by nine point method, with increasing specimen thickness of CT specimen of 50 mm width at different pre-crack depths are shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 71%
“…6 steel of different thicknesses and pre-crack depths, against those measured by nine point method to show that nine point method gives a fairly good estimate of the average SZW measured over closer intervals. Schwalbe et al (1993) has similarly concluded on the basis of round 46 S. Bansal et al The variations of SZW, obtained by nine point method, with increasing specimen thickness of CT specimen of 50 mm width at different pre-crack depths are shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 71%
“…The second macro, 3‐D reconstruction for 5 equally spaced profiles (according to EGF P1–87D method) , was created to compute a sequence of elevation profiles over a region of the fracture surface. It uses the EGF P1–87D method proposed by the European Group on Fracture to analyse the stretching zone of metallic materials (Schwalbe et al ., 1993). An example of the application of this routine to analyse the stretch zone of Al 7050 is described by Hein et al .…”
Section: The Nih Image Macro Routinesmentioning
confidence: 99%
“…The first macro program, 3-D reconstruction of a complete fracture surface region, computes the elevation by measuring the relative parallax on the whole surface of the central region of projections, with the spatial resolution defined by The second macro, 3-D reconstruction for 5 equally spaced profiles (according to EGF P1±87D method), was created to compute a sequence of elevation profiles over a region of the fracture surface. It uses the EGF P1±87D method proposed by the European Group on Fracture to analyse the stretching zone of metallic materials (Schwalbe et al, 1993). An example of the application of this routine to analyse the stretch zone of Al 7050 is described by Hein et al (1999b).…”
Section: Reconstruction Macrosmentioning
confidence: 99%
“…As in this project no J R -curve was available, an alternative procedure was applied: J i was taken from the intersection of the critical stretch zone, SZW c , with the blunting line, which according to [9,32] is given by a validated analytical solution. The principle is shown in Fig.…”
Section: Mode I Fracturementioning
confidence: 99%